Maṣlaḥah and Its Application in Indonesia Fatwā - Khoiruddin Nasution (Studia Islamika, 1996)
Many experts of classical Malay literature argues that Persian influence is known very well to the traditional Malay literature. This is evident from a number of Malay literary texts are very popular, such as Saga Bakhtiar, Hikayat Amir Hamzah, Hikayat Muhammad Hanafiyah and a thousand books is a known problem that some sort of adaptation or even a direct translation of Persian texts.DOI: 10.15408/sdi.v3i4.793